Can AI Replace Human Judgment in Healthcare? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence (AI) into healthcare has sparked a dynamic and often polarized debate. From diagnostic imaging to personalized tre...
Keywords: AI Ethics in Healthcare; Replace; Human; Judgment; Artificial Intelligence; Healthcare; Diagnostics